The general mRNA exporters Mex67 and Mtr2 play distinct roles in nuclear export of tRNAs in Trypanosoma brucei - Hegedusova, Eva; Kulkarni, Sneha Sunil; Burgman, Brandon; Alfonzo, Juan D.; Paris, Zdeněk (Oxford University Press, 2019)
Transfer RNAs (tRNAs) are central players in protein synthesis, which in Eukarya need to be delivered from the nucleus to the cytoplasm by specific transport receptors, most of which belong to the evolutionarily conserved beta-importin family. Based on the available literature, we identified two candidates, Xpo-t and Xpo-5 for tRNA export in Trypanosoma brucei. However, down-regulation of expression of these genes did not disrupt the export of tRNAs to the cytoplasm. In search of alternative pathways, we tested the mRNA export complex Mex67-Mtr2, for a role in tRNA nuclear export, as described previously in yeast. Down-regulation of either exporter affected the subcellular distribution of tRNAs. However, contrary to yeast, TbMex67 and TbMtr2 accumulated different subsets of tRNAs in the nucleus. While TbMtr2 perturbed the export of all the tRNAs tested, silencing of TbMex67, led to the nuclear accumulation of tRNAs that are typically modified with queuosine. In turn, inhibition of tRNA nuclear export also affected the levels of queuosine modification in tRNAs. Taken together, the results presented demonstrate the dynamic nature of tRNA trafficking in T. brucei and its potential impact not only on the availability of tRNAs for protein synthesis but also on their modification status.
Keywords: saccharomyces-cerevisiae; maturation; cytoplasm; transport; receptor; homolog; encodes; import; los1